EMLA-Induced Skin Wrinkling for the Detection of Diabetic Neuropathy - Ng, Wei Ping; Lee, Kok Onn; Shen, Liang; Ong, Jonathan; Nyein Nyein, Thaw Dar; Wilder-Smith, Einar P. (Frontiers in Neurology, 2013)
Objective To determine the usefulness of Eutectic Mixture of Local Anesthetic (EMLA)-induced stimulated skin wrinkling (SSW) to detect diabetic sensorimotor polyneuropathy (DSPN). Research Design and Methods 210 diabetics were prospectively recruited (mean age 58.5±12.7 years) from a large tertiary center from 2009 to 2011. EMLA was applied to the tips of digits 2, 3 and 4 and the degree of wrinkling graded. Diabetic Neuropathy Symptom (DNS) score, nerve conduction studies (NCS), Semmes-Weinstein monofilament (SWMF) tests, and vibratory perception thresholds (VPT) testing were chosen as comparative clinical standards to diagnose length-dependent DSPN. Results Inter-rater agreement for 2 examiners of SSW was high, with Cohen’s weighted Κ of 0.912 for the right hand, and 0.823 for the left. K measure of agreement of SSW with the NCS, DNS scores, SWMF testing and VPT testing was 0.486, 0.243, 0.289 and 0.395 respectively. SSW was able to distinguish between normal and abnormal NCS and DNS results, with median scores of 3.333 vs 1.667 (p<0.0005); and 3.167 vs 2.000 (p<0.0005) respectively. Following ROC analysis, at a cut-off point of < 3 for an abnormal SSW test, sensitivity of SSW test for diagnosing DSPN using NCS as a reference standard was 81.3%, and specificity was 67.0%, on par with other testing methods. Conclusions Stimulated skin wrinkling shows comparable sensitivity to other methods for detecting DSPN. Given its low cost and easy administration, SSW can be considered a useful alternative screening method for diagnosing diabetic neuropathy.